ERP implementation success framework for developing countries : case of South African SMEs - Irakoze, Gloria (Department of Information Systems, 2016)
Enterprise resource planning (ERP) systems have been highlighted in literature as one of the most powerful tools in information systems to facilitate rapid decision-making, cost reduction and greater managerial control. With today's Information Technology (IT) market growth, South African Small and Medium Enterprises (SMEs) have started to recognise ERP systems as a common and necessary platform. However, literature on this topic indicates that the majority of implementations do not meet organisations' expectations. Recent research studies indicate that more than a half of ERP implementations in SMEs fail. More importantly, the factors associated with ERP implementation success in South African SMEs are largely unknown. Furthermore, the high rate failure of ERP implementation in SME represent a threat to South Africa since SMEs are the backbone of the nation's economy. This research study therefore explores success implementation indicators and factors associated with ERP implementation in South African SMEs. In addressing the research questions, the study draws on a combination of the DeLone and McLean IS success model and the Technological, Organisational, Environmental (TOE) framework as well as a number of success factors identified through an extensive review of literature. Semi-structured interviews and thematic analysis are used to collect, analyse the data and to develop the ERP implementation success framework. The ERP implementation success framework is composed of four Information System (IS) success indicators and thirteen success factors. Although, findings established that there are relationships between four IS success indicators and thirteen success factors, only nine of the thirteen success factors were found to have direct relationships with the IS success indicators. The nine success factors are: ERP flexibility, ERP suitability, data accuracy, timeliness, top management support, change management, project management, user training and vendor support. The IS indicators from which these nine factors are related to: Management quality, system quality, information quality and service quality.